Ayurveda, the science of life : a profile and focus on research and development. (Central Council for Research in Ayurveda and Siddha, Union Ministry of Health and Family Welfare, 1986)
Chiefly on the Ayurvedic medico-botanical resources of India and the history and research activities of the Central Council for Research in Ayurveda and Siddha.